1987
DOI: 10.2527/jas1987.653830x
|View full text |Cite
|
Sign up to set email alerts
|

Lasalocid and Dietary Sodium and Potassium Effects on Mineral Metabolism, Ruminal Volatile Fatty Acids and Performance of Finishing Steers

Abstract: Thirty Angus steers averaging 357 kg were used to: 1) determine the effect of feeding lasalocid (33 mg/kg diet) on mineral metabolism and 2) determine the effects of varying dietary sodium (Na) and potassium (K) on finishing steers fed lasalocid. Treatments consisted of: 1) control (.25% Na, .5% K); 2) lasalocid (.05% Na, .5% K); 3) lasalocid (.25% Na, .5% K); 4) lasalocid (.05% Na, 1.4% K) and 5) lasalocid (.25% Na, 1.4% K). Ruminal fluid and blood samples were collected on d 28 and 90 of the 102-d study. Gai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
4

Year Published

1990
1990
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 19 publications
0
2
1
4
Order By: Relevance
“…Since the effects of ionophores may be influenced by K level (Dawson and Boling 1987;Spears and Harvey 1987;Hill 1988) their results may not be directly comparable to the present study. Devlin et al (1969) reported For personal use only.…”
contrasting
confidence: 56%
“…Since the effects of ionophores may be influenced by K level (Dawson and Boling 1987;Spears and Harvey 1987;Hill 1988) their results may not be directly comparable to the present study. Devlin et al (1969) reported For personal use only.…”
contrasting
confidence: 56%
“…De acordo com estes resultados, o período de adaptação (tempo decorrido desde o início de fornecimento de lasalocida) não apresentou efeito sobre a concentração total de AGV. Spears & Harvey (1987) também não encontraram efeito da lasalocida sobre a concentração total de AGV, após 28 dias do início do experimento. Contrariamente, Weiss & Amiet (1980) observaram efeito do ionóforo aos sete dias de aplicação, mas não mais aos 28 ou aos 98 dias após o início do experimento, sugerindo assim um possível efeito de adaptação da flora bacteriana ruminal à lasalocida, com o passar do tempo.…”
Section: Resultsunclassified
“…O ionóforo lasalocida, quando consumido pelos ruminantes, tem apresentado efeitos bastante variá-veis sobre certos parâmetros de fermentação ruminal (Spears & Harvey, 1987). A lasalocida provoca alteração na flora microbiana do conteúdo do rúmen, incrementando as bactérias gram-negativas e provocando diminuição acentuada nas gram-positivas, sendo esta modificação responsável pelas alterações na fermentação ruminal (Chen & Wollin, 1979;Block & Burchard, 1998).…”
Section: Introductionunclassified
See 2 more Smart Citations